SDSS-IV MaNGA: Internal mass distributions and orbital structures of early-type galaxies and their dependence on environment. Issue 2 (4th November 2019) - Jin, Yunpeng; Zhu, Ling; Long, R J; Mao, Shude; Wang, Lan; van de Ven, Glenn
ABSTRACT: In our earlier 2019 paper, we evaluated the reliability of Schwarzschild's orbit-superposition dynamical modelling method in estimating the internal mass distribution, intrinsic stellar shapes and orbit distributions of early-type galaxies (ETGs) taken from the Illustris cosmological simulation. We now apply the same techniques to galaxies taken from the integral-field survey Mapping Nearby Galaxies with APO (MaNGA), using a sample of 149 ETGs in the mass range of 10^9.90\!-\! 10^11.80 M_ and made up of 105 central and 44 satellite galaxies. We find that low-mass ETGs with log ( M * /M⊙ ) < 11.1 have an average dark matter fraction of ∼0.2 within one effective radius R e, tend to be oblate-like, and are dominated by rotation about their minor axis. High-mass ETGs with log ( M * /M⊙ ) > 11.1 have an average dark matter fraction of ∼0.4 within one effective radius R e, tend to be prolate-like, and are dominated by rotation about their major axis and by centrophilic orbits. The changes of internal structures within one R e are dominated by the total stellar mass of the individual galaxies. We find no differences of internal structures between central and satellite ETGs for the same stellar masses. However, for similar stellar mass and colour distributions, we find that ETGs more prolate-like, or with more hot orbits, tend to have higher close neighbour counts at rp ∼ 40 kpc.